2019
DOI: 10.15280/jlm.2019.9.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity and Its Associated Factors among School Children in Udupi, Karnataka, India

Abstract: BackgroundChildhood obesity has become a serious public health problem in many low-and-middle income countries. This study aims to determine the prevalence and assess the factors associated with obesity among school children.MethodsA cross-sectional school-based study was conducted among the 1185 secondary school students in Udupi, India. Data were collected using self-administered questionnaires. Weight and height were measured and Body Mass Index (BMI) was calculated. The z-score was calculated, and BMI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
2
20
1
Order By: Relevance
“…In the Udupi study, there was no statistical correlation between frequent consumption of carbonated drinks and being overweight/obese [16]. But in Oceania, Pengpid and Peltzer found that consumption of >1 carbonated drink per day increased OR for obesity by 1.32 (95% CI 1.09-1.61, p < 0.01) [11].…”
Section: Dietary Factorsmentioning
confidence: 89%
See 4 more Smart Citations
“…In the Udupi study, there was no statistical correlation between frequent consumption of carbonated drinks and being overweight/obese [16]. But in Oceania, Pengpid and Peltzer found that consumption of >1 carbonated drink per day increased OR for obesity by 1.32 (95% CI 1.09-1.61, p < 0.01) [11].…”
Section: Dietary Factorsmentioning
confidence: 89%
“…Ramachandran et al reported the prevalence of overweight to be 17% in boys and 15.8% in girls in the age group 13-18 years from Chennai [25]. In the study from Udupi in South India, the prevalence of overweight and obese were 11.0 and 7.1%, respectively, in boys and 10.6 and 5.4%, respectively, in girls [16]. Researchers from Wardha, in Central India, reported the prevalence of overweight/ obesity to be 4.4% in boys and 4.3% in girls [17].…”
Section: Gendermentioning
confidence: 93%
See 3 more Smart Citations